Demographic Dividend and Labour Market Dynamics: An Empirical Analysis of Socio-Economic Transition and Policy Implications - Tsintsadze, Asie; Glonti, Vladimer; Diasamidze, Merab; Ghoghoberidze, Tamar (Dr. Viktor Koval, 2025)
Introduction. Despite macroeconomic improvements, Georgia has faced a persistent negative demographic dividend that has held back economic growth over the past two decades. This study combines dependency ratios, unemployment, self-employment, and informal employment characteristics using an innovative algorithm. Considering its unique informal sector, this approach provides a more realistic picture of Georgia’s demographic and economic dynamics. Aim and tasks. This study aims to empirically assess the impact of the demographic situation in Georgia on labour market dynamics and the socio-economic transition using a modified algorithm, regression analysis, and CGE modelling to identify necessary reforms and develop evidence-based policy recommendations to facilitate the realisation of the demographic dividend. Results. The study confirms that, despite GDP and wage growth, Georgia has experienced a persistently negative demographic dividend over the past two decades. Traditional dependency ratios fail to reflect the specifics of Georgia’s highly informal and underemployed labour market. Regression analysis and the Granger causality test show that dependent unemployment and cost increases are the key drivers behind the negative trend. Empirical data show a decline in net demographic returns: -€35.96 million (2002-2012) and -€89.91 million (2013-2023), indicating that employees are unable to pay dependent expenses, especially in 2022. Regression (R² = 96%) confirmed the negative impact of dependency burden and expenses, while the falling birth rate had only a weak offsetting effect. Granger tests revealed that the size of the dependent population, food expenditures and mortality rates predict future dividend values, confirming the relevance of the planning model. Evidence strongly suggests that without structural reforms in labour, social, and health policies and productivity boosts, Georgia’s demographic trends will continue to hinder economic growth rather than support it. Conclusions. The study concludes that without targeted reforms in the labour market, healthcare, and economic planning, Georgia will not be able to turn demographic changes into economic benefits. The presented model emphasises the influence of demographic factors on socio-economic development and the importance of aligning demographic trends with effective economic policies.